Is the Spiritual Intelligence of Parents Related to Youth's Emotional Status and Sexual Behavior? - Ardhian Indra Darmawan; Titih Huriah (Universitas Muhammadiyah Semarang, 2020)
Related Research spiritual intelligence of parents with emosioal status and sexual behavior of teenagers. The purpose of knowing the relationship of sexual behavior and emotional status of adolescents with the spiritual intelligence of parents in work area Puskesmas Kasihan I. This study used a mix method design with sequential explanatory. Quantitative respondents were 132 adolescents and parents. Analysis of the data used in this quantitative study was control tau. The qualitative participants were 11 teenagers. Research interviews were conducted on 11 student participants who were taken by purposive sampling and qualitative data analysis using invivo software. The instrument used was the Spiritual Self-Report Inventory (SISRI), Strengths and Difficulties Questionnaire (SDQ), Sexual Behavior. Qualitative instruments use interview guides, telephone and observation sheets. The results showed that 101 adolescents with abnormal emotional status, 15 boderlines, 4 normal respondents. Adolescent sexual behaviors that are positive or active are 44 teenagers and 89 adolescents are negative or inactive behaviors. Found three factors that influence the emotional status and sexual behavior of adolescents, namely the role of moral education from parents, social control and adolescent self-control ability. The role of parents, the environment and adolescent self control affect the emotional status and sexual behavior of adolescents.